Study of prevalence and factors associated with Maternal Near Miss (MNM) cases and maternal death at Rajiv Gandhi Government Women and Children Hospital, Pondicherry, India - H. J., Rakesh; Diana, Valsa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Maternal mortality is a critical event to assess the quality of a health care system. Analysing the maternal near miss provides a good opportunity for assessing the factors responsible for maternal mortality in that area. The objective of this study was to study the clinic-etiological profile of severe maternal morbidity/near miss case in a tertiary public maternity hospital using criteria from maternal near miss review operational guidelines Ministry of Health and Family Welfare, Government of India (2014). Methods: A prospective observational study included patients admitted to Rajiv Gandhi Government Women and Children Hospital, Pondicherry between August 2016 and July 2017. The patients who met Near Miss Criteria (a set of Clinical, Laboratory and Management based criteria) given by MoH and FW, Government of India (2014) were enrolled; their clinical and investigation parameters were recorded. Results: Out of 9583 live births, 27 (0.281%) were near-miss cases. The maternal near miss incidence ratio was low 2.81 /1000 live births, because of strict criterion of labelling near-miss cases. Maternal near miss to mortality ratio was 13.5:1, and mortality index was 6.89%, lower the index, indicates better quality of care. The mean age of the near-miss patients was 27.75 years. Most of the patients of near-miss were of multipara n = 17 (62.96%). Majority n = 16 (59.25%) of patients were at term gestation. The major causes of near miss were severe haemorrhage n = 11 (42%), Hypertension n = 9 (35%) and rupture uterus n = 4 (15%). Major intervention peripartum hysterectomy was needed in n = 7 (27%) and stepwise devascularisation only in another n = 5 (19 %) of near miss cases. Conclusions: Haemorrhage was the leading cause of near miss events. The study of maternal near miss provides an insight into the causes of maternal mortality in this region. The maternal morbidity and mortality can be reduced by providing proper antenatal care at primary and community health centre level and good intensive care and using maternal early warning system (MEWS) at tertiary level. Maternal near miss ratio is worth presenting in national indices.